Pengaruh Desain Produk dan Gaya Hidup terhadap Keputusan Pembelian Tumbler Rosca di Kalangan Generasi Z Kota Banjarmasin - Melsa Erliana; Irwansyah; Siti Rusidah; Novia Nour Halisa (Business Administration, FISIP ULM, 2026)
Melsa Erliana, 2210412220041, 2026. The Influence of Product Design and Lifestyle on the Purchasing Decisions of Rosca Tumblers among Generation Z in Banjarmasin City, under the supervision of: Irwansyah. The increasing use of tumblers among Generation Z has made this product not only a drinking container but also part of daily needs and lifestyle trends. Attractive product design and consumer lifestyle are factors that can influence purchasing decisions for Rosca Tumblers among Generation Z in Banjarmasin City. This study aims to determine and examine the influence of product design and lifestyle on the purchasing decisions of Rosca Tumblers among Generation Z in Banjarmasin City. This research employed a quantitative approach. The sample consisted of 100 Generation Z respondents who had purchased and used Rosca Tumblers, selected using a purposive sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the Statistical Package for the Social Sciences (SPSS) software. The results showed that product design and lifestyle had a positive and significant effect, both partially and simultaneously, on purchasing decisions of Rosca Tumblers among Generation Z in Banjarmasin City.